NATURAL COURSE OF CHRONIC VIRAL HEPATITIS B AND C IN CHILDREN - Isakulova Muhabbat Mardanovna; Ibragimova Nadiya Sabirovna; Isomadinova Lola Kamoliddinovna; Pardayeva Shahlo Abriy Qizi (TADQIQOTLAR.UZ, 2024)
Annotation. Chronic viral hepatitis is a pressing problem in modern healthcare, due to the almost universal spread of this infection and the high risk of developing unfavorable outcomes. The most difficult group is represented by patients with mixed hepatitis, which is associated with more rapid progression of the disease and the development of liver cirrhosis. The article presents data from long-term observation of children with chronic hepatitis B+C (CHB+C), demonstrates the features of the clinical course, the nature of biochemical, immunological, morphological changes in the natural course of the disease.